Health Policy on the Town Meeting Agenda - Hines, Brian (The Hastings Center report, 1986)
American Health Decisions, a movement that started in Oregon, has spread to several other states. Through the media and widespread public discussion, the projects aim to increase public awareness about the individual and societal dimensions of ethical choices in health care.